2012
DOI: 10.1055/s-0031-1298453
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Aloes: Antioxidant, Antiproliferative, and Immunostimulatory Attributes

Abstract: Aloe is a genus of medicinal plants with a notable history of medical use. Basic research over the past couple of decades has begun to reveal the extent of Aloe?s pharmaceutical potential, particularly against neoplastic disease. This review looks at Aloe, both the genus and the folk medicine, often being called informally ?aloes?, and delineates their chemistry and anticancer pharmacognosy. Structures of key compounds are provided, and their pharmacological activities reviewed. Particular attention is given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 41 publications
0
62
0
1
Order By: Relevance
“…Among them, Aloe vera (L.) Burm.f. (Aloaceae) (aloe) is a genus of medicinal plants with a history of medical use for several thousand years (Boudreau et al, 2013;Harlev et al, 2012). Its antineoplastic property is due to at least three different mechanisms based on antiproliferative, immunostimulatory, and antioxidant effects, whereas the antiproliferative action is determined mainly by the anthraquinonic molecules, such as aloin and emodin (Harlev et al, 2012).…”
Section: Herbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, Aloe vera (L.) Burm.f. (Aloaceae) (aloe) is a genus of medicinal plants with a history of medical use for several thousand years (Boudreau et al, 2013;Harlev et al, 2012). Its antineoplastic property is due to at least three different mechanisms based on antiproliferative, immunostimulatory, and antioxidant effects, whereas the antiproliferative action is determined mainly by the anthraquinonic molecules, such as aloin and emodin (Harlev et al, 2012).…”
Section: Herbsmentioning
confidence: 99%
“…(Aloaceae) (aloe) is a genus of medicinal plants with a history of medical use for several thousand years (Boudreau et al, 2013;Harlev et al, 2012). Its antineoplastic property is due to at least three different mechanisms based on antiproliferative, immunostimulatory, and antioxidant effects, whereas the antiproliferative action is determined mainly by the anthraquinonic molecules, such as aloin and emodin (Harlev et al, 2012). Aloin, an anthraquinone glycoside derived from aloe leaves, has shown to inhibit human cervical, breast, and ovarian cancer cells as well as leukemia cells, exerting also antiangiogenic properties (Harlev et al, 2012;Niciforovic et al, 2007;Pan et al, 2013).…”
Section: Herbsmentioning
confidence: 99%
See 1 more Smart Citation
“…These defense systems include phytochemicals (secondary metabolites) endowed with remarkable bioactivities (Chawla et al, 2012;Croteau et al, 2000;Harlev et al, 2012a;Wang et al, 2007). The high concentrations of defensive metabolites in desert plants are known to impart antioxidant, anti-inflammatory, antimutagenic, antiviral, antifungal and antimicrobial capabilities to the plant, and also block detrimental UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by numerous authors (Ognik and Sembratowicz 2007;Akhtar et al 2012;Ognik and Sembratowicz 2012a) have confirmed the beneficial effect of aloe extracts on the immune response in poultry. The immunostimulatory properties of the aloe preparation may be linked to the presence of acemannan polysaccharides in aloe (Harlev et al 2012), as well as the vitamin C included in the formulation, whose role in the immune reaction is well known. Ascorbic acid is necessary for phagocytic reactions to proceed properly, and also stimulates interferon synthesis and lymphocyte proliferation (Ortuño et al 2001).…”
Section: A Bmentioning
confidence: 99%